Resonance scattering generated by rotating bodies; Physica Scripta; Vol. 99 - Li Renxian; Tang Huan; Wei Bing; Gong Shuhong; Ruiping Yang; Shi Zhuoyuan; Zhang Yuan; Yuexiao Jiao; Li Xiao; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich (2024, 2024)
Title screen